Ce–Dy substituted barium hexaferrite nanoparticles with large coercivity for permanent magnet and microwave absorber application. (13th May 2021) - Todkar, G B; Kunale, R A; Kamble, R N; Batoo, Khalid M; Ijaz, M F; Imran, A; Hadi, M; Raslan, E H; Shirsath, Sagar E; Kadam, R H
Abstract: M-type barium hexaferrites (BaM) with the substitution of Ce–Dy ions were synthesized using the sol-gel auto-ignition method. The prepared materials were explored for their application as a permanent magnet and microwave absorbing material. The structural properties, phase evaluation, micro-strain, morphological analysis, magnetic behaviour, microwave absorbing properties and optical properties were studied by employing various techniques. The structural parameters and phase identification obtained by Rietveld refinement confirmed the formation of an M-type hexaferrite structure for pure BaM, whereas Ce–Dy substitution induced secondary phases of cubic CeO2 and ortho DyFeO3 . Crystallite size obtained from Williamson–Hall plots increased from 27.1 nm to 30.8 nm with the introduction of Ce–Dy ions in BaM. The nanocrystalline nature of the prepared samples was confirmed using scanning and transmission electron microscopy techniques. Fourier transform infrared spectra of all the samples were recorded in the wavenumber range of 400–4000 cm −1 and also supported the x-ray diffraction findings by confirming the formation of samples with hexaferrite structures. Coercivity of the BaM hexaferrites improved from 4430 to 5721 Oe with the Ce–Dy substitution. A Ce–Dy substituted BaM hexaferrite sample of 3 mm thickness showed a maximum reflection loss of −16.3 dB around 16.7 GHz. Permittivity and permeability studies were carried out to understand the microwave absorption behaviour.